Analysis of Budget Execution Performance: A Case Study of Work Units within the Jurisdiction of the Bogor State Treasury Service Office - Muchamad Amrullah (CV Edujavare Publishing, 2026)
Budget execution performance indicators serve as instruments to measure the budget execution performance of work units and reflect the strengthening of